Genetic mapping for agronomic traits in a MAGIC population of common bean (Phaseolus vulgaris L.) under drought conditions - Díaz, Santiago; Ariza-Suárez, Daniel; Izquierdo, Paulo; Lobaton, Juan David; Hoz, Juan Fernando de la; Acevedo, Fernando; Duitama, Jorge; Guerrero, Alberto F.; Cajiao V., César Hernando; Mayor, Victor; Beebe, Stephen E.; Raatz, Bodo (Springer, 2020)
Background Common bean is an important staple crop in the tropics of Africa, Asia and the Americas. Particularly smallholder farmers rely on bean as a source for calories, protein and micronutrients. Drought is a major production constraint for common bean, a situation that will be aggravated with current climate change scenarios. In this context, new tools designed to understand the genetic basis governing the phenotypic responses to abiotic stress are required to improve transfer of desirable traits into cultivated beans.